Pengembangan Instrumen Penilaian Digital Untuk Mengukur Hasil Belajar IPS Kelas IV Sekolah Dasar - Ratna Widya Wijayanti; Yatim Riyanto; Waspodo Tjipto Subroto (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Students are accustomed to doing evaluations with sheets of paper will have difficulty when working on Computer-Based School Exams and greatly affect the results they get. Students are a digital native generation where in their daily life they are surrounded by sophisticated digital devices and always use digital technology in their daily lives. Therefore, it is time for teachers to innovate by developing digital assessment instruments that are innovative, interesting and help students measure their learning outcomes. Based on this, this study aims to develop a digital assessment instrument that has feasibility, practicality and effectiveness in measuring social studies learning outcomes for Grade IV elementary schools. This study uses research and development methods or Education Research and Development (RnD) and learning outcomes trials using pre-test and post-test. Data collection techniques used in this study were observation, interviews, expert validation, student response questionnaires and learning outcomes acquisition tests (pretest and posttest). The data analysis technique used is descriptive quantitative. The results of the validation phase of this digital assessment instrument have a fairly high validity and feasibility. The results of the assessment from media experts obtained a percentage of 96% validity, the results of assessments from material content experts obtained a total validity percentage of 91%, practicality tests from fourth grade teachers obtained a percentage of 99% and the results of the responses or responses of students in the field obtained a practical percentage of 98% entirely. The level of effectiveness of the digital assessment instrument can be seen from the comparison of the pretest which gets an average value of 64.2 while the posttest gets an average value of 85.8. Thus, it can be concluded that this digital assessment instrument has feasibility, practicality and effectiveness in measuring social studies learning outcomes for grade IV Elementary School.